Threshold effect of visceral adiposity index on suicidal ideation: a mediation analysis through fasting blood glucose - Zhang, Li; Zhang, Wenhao; Hang, Lihua (Frontiers in Psychiatry, 2025)
ObjectiveThe complex interplay between visceral adiposity and mental health outcomes, particularly suicidal ideation, remains a critical yet understudied area.MethodsThis cross-sectional analysis utilized data from the National Health and Nutrition Examination Survey (NHANES 2005-2018), examining 11,931 adults aged ≥20 years. Visceral adiposity index (VAI) was calculated using sex-specific equations. Suicidal ideation was assessed using item 9 of the Patient Health Questionnaire-9 (PHQ-9). We employed multivariable logistic regression models, generalized additive models (GAM), threshold effect analysis using segmented regression, and mediation analysis via fasting blood glucose (FBG) with 5,000 bootstrap resamples.ResultsA significant non-linear association between VAI and suicidal ideation was identified, with a threshold effect at VAI=6.81 (likelihood ratio test, P=0.006). Below this threshold, each unit increase in VAI was associated with 9.4% higher odds of suicidal ideation (OR=1.094, 95% CI: 1.028-1.163, P=0.005), while no significant association was observed above the threshold. FBG mediated 31.74% (95% CI: 4.43%-181.74%) of this relationship. The association was particularly pronounced among older adults (≥60 years), females, and individuals with diabetes or hypertension.ConclusionsThese findings highlight the importance of considering visceral adiposity in mental health assessments, especially among vulnerable populations, and suggest potential metabolic pathways linking adiposity to mental health outcomes through glucose metabolism.